Atom-efficient chlorination of benzoic acids with PCl3 generating acyl chlorides. Issue 5 (May 2019) - Xiao, Jing; Han, Li-Biao
By using PCl3 as the chlorinating reagent, various carboxylic acids are converted into the corresponding acid chlorides in good yields. This method features high atom efficiency in which nearly all three chlorine atoms of PCl3 are used in the chlorination. Moreover, the work-up procedure is simple since the major side product is phosphonic acid [HP(O)(OH)2 ] which is non-toxic and easily removed by filtration. A possible mechanism is proposed in this paper.